Inhalable and respirable dust mass concentration on soiled inorganic artefacts at the National Museum Malaysia - Mohd. Din, Shamzani Affendy; Kolapo, Otuyo Muhsin; Othman, Rashidi (2019)
Particulate matter (PM) plays a crucial role in altering the air quality, human health and materials. PM does not only affect human health but damages the museum's artefacts in many ways such as paint and materials deterioration, metal corrosion, fading of dyes and soiling of stone rubber, and textile. The main aim of this research is to quantify the mass concentration of suspended particulate matter in terms of respirable and inhalable particles at outdoors, indoors, and exhibition boxes of the National Museum Malaysia. This research was conducted for 32 days (16 weekdays and 16 weekends). The main target exhibition boxes for this research were those containing inorganic-based materials such as metals, stones, and ceramics. In total, 12 sample stations were surveyed, this includes three exhibition boxes each from Gallery A and B, an indoor area of both Gallery A and B, lobby and three outdoor locations at the front entrance, rear entrance, and right-wing of the building. Cyclone sampler head and Casella 7-Holes were used to capture respirable and inhalable samples, respectively. Result revealed that most of the average mass concentration obtained in all sample stations were beyond limited guidelines stated by the Department of Safety and Health (DOSH) and Department of Environment (DOE). The average mass concentrations of inhalable dust sampled at the metal and ceramic exhibition box of Gallery A at weekdays were the highest with an average mass concentration value of 0.4688 mg/m3, which is about 213 % more than the required standards. However, lower values were obtained for the respirable particles, but they were found to still beyond standard DOE guidelines for PM10. The highest respirable particles were found at the ceramic exhibition box of Gallery A with 0.3788 mg/m3 average mass concentration. The result of respirable dust to the total inhalable dust were 55.4 % and 59.7 % for weekdays and weekends, respectively. The concluding part highlights recommendations on ways to reduce the transfer PM into the indoor area of the museum to reduce soiling defects. DOE, DOSH, as well as the Ministry of Natural Resources and Environment (MONRE), can use the result of this research to come up with a procedure to reduce the effect of airborne particulate matter on the museum artefacts. Hence, reducing government expenses by reducing the total cost of cleaning procedure toward damaged artefacts. Additionally, this study is beneficial to conservationists, museum management and curators by enlightening them on ways to reduce the damaging effect caused by airborne particulate matter.